2014
DOI: 10.18632/oncotarget.1871
|View full text |Cite
|
Sign up to set email alerts
|

Biglycan enhances gastric cancer invasion by activating FAK signaling pathway

Abstract: Biglycan (BGN) is an important member of small leucine-rich proteoglycans family, and has been implicated in oncogenesis and development of various human cancer types. Here we report that BGN promotes tumor invasion and metastasis of gastric cancer both in vitro and in vivo. BGN expression is significantly higher in gastric cancer tissues and associated with lymph node metastasis, depth of tumor invasion and TNM stage. BGN enhances gastric cancer cell wound healing, migration and invasion ability as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
120
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(126 citation statements)
references
References 26 publications
6
120
0
Order By: Relevance
“…Biglycan is an important component of the extracellular matrix. Mounting evidence supports the hypothesis that biglycan fulfils an oncogenic role in gastric cancer, and gastric cancer cells exhibited increased motility and invasive properties upon biglycan overexpression (17). In the present study, the shRNA-mediated knockdown of biglycan markedly reduced the spontaneous migration distance and the number of invasive colon cancer cells.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Biglycan is an important component of the extracellular matrix. Mounting evidence supports the hypothesis that biglycan fulfils an oncogenic role in gastric cancer, and gastric cancer cells exhibited increased motility and invasive properties upon biglycan overexpression (17). In the present study, the shRNA-mediated knockdown of biglycan markedly reduced the spontaneous migration distance and the number of invasive colon cancer cells.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies demonstrated that biglycan exerts a distinct role in different tumor entities (15)(16)(17). To further investigate the underlying mechanism of biglycan in colon cancer, the effect of biglycan on colon cancer cell migration and invasion was determined.…”
Section: Downregulation Of Biglycan Suppresses the Migratory And Invamentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study has found that BGN was higher expressed in endometrial cancer cells, and we also know that carcinomatous stroma and the up-regulation of BGN was significantly associated with poor tumor differentiation and advanced stage of the tumor [13]. Growing evidence has demonstrated that BGN gene is overexpressed in various carcinoma tissues such as pancreatic adenocarcinoma [8], colon tumor [9], intrahepatic cholangiocarcinoma [11], gastric cancer [12], esophageal squamous cell carcinoma [14], and melanoma [15], which have something to do with disease progression in some respects. High BGN levels are harmful in tissue and are considered to shortening patients' survival.…”
Section: Discussionmentioning
confidence: 96%
“…BGN is found to be expressed on the cell surface and in the extracellular matrices of some specialized cell form, and it is distributed widely, basically presents in every organ in human body, although there is uneven within each organ [6,7]. Recently higher expression of BGN has been detected in several tumor tissue compared with the normal tissue such as pancreatic adenocarcinoma [8], colon tumor [9], ovary cancer [10], intrahepatic cholangiocarcinoma [11], and gastric cancer [12]. The overexpression of BGN in tumor tissues suggests a significant role of BGN in cancer metastasis and progression.…”
Section: Introductionmentioning
confidence: 99%